Testing Fiscal Sustainability in the Republic of Macedonia - A VAR Approach - Tashevska, Biljana; Trenovski, Borce (Varazdin Development and Entrepreneurship Agency, Varazdin, Croatia; Faculty of Management University of Warsaw, Warsaw, Poland; University North, Koprivnica, Croatia, 2017)
The recent global financial and economic crisis caused great concerns in many developed countries (especially in the European Union) due to rising debt levels and deterioration of their fiscal space. The adverse effects of high indebtedness highlighted the importance of maintaining sustainable public finances. This problem was not limited to rich and highly developed economies. The Republic of Macedonia also experienced such developments in the fiscal area and the public debt ratio doubled in the last decade. The aim of this paper is to investigate the fiscal sustainability of Macedonia using quarterly data for the period 2005 – 2016. We use a VAR model to determine whether the primary balance responds positively to increases in government indebtedness, thus ensuring fiscal sustainability, or is set exogenously and independently from changes in government liabilities. The empirical analysis shows that the primary balance lacks the necessary and sufficient positive response to an increase in the government debt level that helps prevent a further debt accumulation. These results, together with the drastically increased public debt since 2008, imply a need for a faster adjustment of the primary balance after a government debt shock in order to prevent reaching even higher debt levels and losing a valuable fiscal space
Keywords: fiscal reaction function, fiscal sustainability, primary balance, government debt, VAR